Plication: an innovative method of treating piles - Pattanayak, Sibaprashad; Kumar, Manish; Patro, Santosh Kumar; Behera, Manoj Kumar (International Surgery Journal, 2019)
Background: The cause of haemorrhoids remains unknown. Factors contributing to haemorrhoids are constipation, prolonged squatting, pregnancy, aging, heredity, portal hypertension, abdominal tumour etc. Methods: This prospective study was carried out in department of surgery, M.K.C.G MCH, Berhampur, Odisha, India from 01st August 1995 to 31st July 2017. Patients from both sex and different age groups having haemorrhoids were included. Patients with piles secondary to anorectal tumours, prolapsed and thrombosed piles, anorectal pathology like fissure were excluded from study. Preoperative, intraoperative interventions and postoperative care were carried out according to laid procedure described below. Results: Total 1014 patients of piles were selected for plication and conventional haemorrhoidectomy and most of them were between 31-50 years of age while 362 cases underwent plication, rest 346 cases were treated with haemorrhoidectomy. All patients in this study had bleeding per rectum as the main symptom. Out of 507 patients which has been examined for plication, 272 (53.65%) had 2nd degree, 235 (46.35%) had 3rd degree piles. Results of plication of piles are satisfactory and only 4% patients had pain for which long term analgesics were given. Conclusions: Treatment of haemorrhoids is well debated topic and various methods are being used by surgeons all over world. Plication of piles appears to have significant advantages over conventional methods in terms of patient comfort, duration of stay in hospital and incidence of complications. Literature on this subject is briefly reviewed.